Relationship Between Nanoindentation and Wear Properties of Stainless Steel-Reinforced Aluminium Matrix Composite - Gecu, Ridvan; Karaaslan, Ahmet (SPRINGER/PLENUM PUBLISHERS, 2017)
304 Stainless steel (SS)-reinforced A356 aluminium matrix composites were manufactured by melt infiltration casting. Recycled SS shavings were pressed to obtain porous monoblock preform, and molten Al alloy was infiltrated into vacancies of the preform during casting process. Various preform preheating times (0-60 min) before casting were studied, and the effect of preheating time on relationship between nanoindentation and wear properties of produced composites was discussed. All casting operations were carried out at 730 degrees C. Fabricated composites were characterized by optical microscope, SEM, FEG-SEM, XRD, EDS, nanoindentation tester and ball-on-disc type tribometer with using -Al2O3 ball as counterpart. theta-Fe4Al13 and eta-Fe2Al5 phases were obtained at the interfaces, except for 60 min preheated sample. These reaction phases increased the hardness, compressive residual stress and consequently wear resistance. On the other hand, when the sample was not preheated or preheated excessively, interface bonding was weakened and crack propagation was occurred. Cracked particles from interfacial phases in these specimens participated wear process and caused increase in wear rate of manufactured composites.
Keywords: Aluminium matrix composite; Melt infiltration casting; Nanoindentation; Wear; Residual stress; MECHANICAL-PROPERTIES; SLIDING WEAR; INSTRUMENTED INDENTATION; TITANIUM CARBIDE; ABRASIVE WEAR; FRETTING WEAR; BEHAVIOR; FRICTION; HARDNESS; STRESS; Engineering